ANALISIS NIAT BELI KONSUMEN MELALUI ONLINE FOOD DELIVERY DI ERA PANDEMIC COVID-19 - Intan Muliana Rhamdhani (Kajian Bisnis Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha, 2021)
Online food delivery (OFD) is an innovative and simple way of purchasing food online. This study aims to examine consumer purchase intentions to use OFD Go-food services during the Covid-19 Pandemic. This study uses a survey of 100 consumers who have the Go-jek application in Kebumen to fill out the questionnaire. The sample technique was taken by using purposive sampling technique, then the data were processed using SPSS version 25.0 and analyzed using path analysis. The findings of this study indicate that the convenience motivation and perceived ease of use are proven unable to directly influence consumer intention to use OFD. Meanwhile, convenience motivation and perceived ease of used have an effect on perceived usefulness. Other results indicate that perceived usefulness is able to act as a mediating variable between convenience motivation, perceived ease of use on consumer purchase intentions using OFD